Teknik Penyadapan Tanaman Karet untuk Efektivitas Hasil Getah Karet (Havea Brasiliensis) - Utary Gladysha Ronasyary (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
Rubber plants (Hevea brasiliensis) are one of the main commodities in the plantation industry which have high economic value. Rubber latex productivity is greatly influenced by the tapping technique applied. This research aims to examine various tapping techniques that are effective in increasing rubber latex yields and maintaining tree productivity in the long term. The method used includes comparative analysis of tapping techniques, such as angle and depth of incision, frequency of tapping, and use of latex stimulants. The research results show that tapping techniques with an angle of 30°–45° and an optimal depth that does not damage the cambium can significantly increase latex production. In addition, the use of ethefon-based stimulants has been shown to extend the latex flow period and increase yields without causing excessive physiological stress in plants. By implementing appropriate tapping techniques, rubber plantation productivity can increase sustainably without reducing the productive life of the plants.